Development of Sol-Gel Process for Synthesis of Single-Walled Carbon Nanotubes - VALIZADEH, M.; KAZEMZADEH, A.; RAISIAN, M.; MOHAMMADIZADEH, A. (Asian Journal of Chemistry, 2010)
Support and catalyst materials have been proved to be critical to scalable chemical vapour deposition (CVD) synthesis of carbon nanotubes. In present study, we found that porous Al2O3, SiO2 prepared by sol-gel process of its organosilane compound and salts was an eminent support for CVD growth of single-walled carbon nanotubes (SWNTS). The quality of as-grown (SWATS) on Al2O3, SiO2 support and Fe, Mo catalyst was stable; the effect of reaction condition such as furnace temperature, flow rate of the gas and type of catalysts and supports on the properties of as (SWNTS). Products were thoroughly investigated and characterize by TEM, SEM, TG and other technologies. The results indicated that the yields of (SWNTS) on Al2O3, SiO2.With Fe and Mo could be up to about 100%. The obtained purify of the as growth product was higher than 85% after treatment with HCl, HNO3 and HF. This advantage of support is efficient and stable growth of (SWNTS).